Performance Differences in Male Youth Basketball Players According to Selection Status and Playing Position: An Evaluation of the Basketball Learning and Performance Assessment Instrument - Rösch, David; Ströbele, Martin G.; Leyhr, Daniel; Ibáñez, Sergio J.; Höner, Oliver (Frontiers in Psychology, 2022)
The Basketball Learning and Performance Assessment Instrument (BALPAI) has been initially developed and evaluated to assess the performance of students or youth basketball players on the entry level. As it is currently the only observational instrument that allows an overall assessment of players’ in-game performance, it might represent a valuable tool for talent identification and development purposes. To investigate this potential field of application, this study aimed to evaluate the BALPAI regarding reliability and diagnostic validity when assessing youth basketball players within a competitive setting. The study sample comprised N = 54 male youth players (Mage = 14.36 ± 0.33 years) of five regional selection teams (Point Guards, PG: n = 19; Shooting Guards and Small Forwards, SG/SF: n = 21; and Power Forwards and Centers, PF/C: n = 14) that competed at the annual U15 national selection tournament of the German Basketball Federation (n = 24 selected; n = 30 non-selected). A total of 1997 ball-bound actions from five games were evaluated with BALPAI. The inter-rater reliability was assessed for technical execution, decision making, and final efficacy. The diagnostic validity of the instrument was examined via mean group comparisons of the players’ offensive game involvement and performance regarding both selection-dependent and position-dependent differences. The inter-rater reliability was confirmed for all performance-related components (κadj ≥ 0.51) while diagnostic validity was established only for specific the BALPAI variables. The selection-dependent analysis demonstrated higher offensive game involvement of selected players in all categories (p < 0.05, 0.27 ≤ Φ ≤ 0.40) as well as better performance in shooting and receiving (p < 0.05, 0.23 ≤ Φ ≤ 0.24). Within the positional groups, the strongest effects were demonstrated among PG (p < 0.05, 0.46 ≤ Φ ≤ 0.60). The position-dependent analysis revealed that PG are more involved in total ball-bound actions (p < 0.05; 0.34 ≤ Φ ≤ 0.53), passing (p < 0.001; 0.55 ≤ Φ ≤ 0.67), and dribbling (p < 0.05, 0.45 ≤ Φ ≤ 0.69) compared to players in other positions. Further differences between players according to selection status and playing position were not detected. The results of this evaluation indicate that the instrument, in its current form, is not yet applicable in competitive youth basketball. The findings highlight the importance of optimizing BALPAI for reliable and valid performance assessments in this context. Future studies should investigate the application of stricter and position-specific criteria to use the observational tool for talent identification and development purposes.